Housing Credit Payment Information System Using the Sliding Rate Method - Farid; Nur Oktavin Idris; A. Mulawati Mas Pratama (JSAI (Journal Scientific and Applied Informatics), 2023)
Housing is a basic need that is essential for human life. Some members of the community rely on home ownership credit facilities (KPR) to achieve homeownership. Therefore, Bank Paro Dana offers KPR to support the increasing housing needs of the community. However, it is important for customers to understand the calculation mechanism and payment system of KPR that are safe and suitable for their needs, as well as to understand the varying interest rates in KPR and be cautious in facing market interest rate uncertainties. The problems encountered so far are the high-interest rates and installments that must be paid. Therefore, an effective and efficient method is needed in managing KPR installment payments, supported by the development of an information system that can automatically and transparently manage monthly installment calculations and assist customers in making payments. Hence, this research aims to implement the sliding rate method in the housing credit payment information system. The testing results using the white box technique obtained V(G) = 2 and Cyclomatic Complexity (CC) = 2, indicating that the proposed system can be concluded as effective and efficient. With the existence of this system, it is expected that the quality of service to customers can be improved through a better information system and provide a positive contribution to the development of the KPR payment system, thus providing maximum benefits for all parties involved